2017
DOI: 10.1177/0954411916683221
|View full text |Cite
|
Sign up to set email alerts
|

Capturing complexity in pulmonary system modelling

Abstract: Respiratory disease is a significant problem worldwide, and it is a problem with increasing prevalence. Pathology in the upper airways and lung is very difficult to diagnose and treat, as response to disease is often heterogeneous across patients. Computational models have long been used to help understand respiratory function, and these models have evolved alongside increases in the resolution of medical imaging and increased capability of functional imaging, advances in biological knowledge, mathematical tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 114 publications
0
8
0
Order By: Relevance
“… Calmet et al , 2018 ; Feng et al , 2016 ; Garcia et al , 2009 ; Keeler et al , 2015 ; Martonen and Wilson, 1983 ; Schroeter et al , 2016 ; Se et al , 2010 ). Fortunately, the time and effort to develop multiple models and perform the computational chemistry and physics processes associated with aerosols in even these complex, transient simulations continue to be reduced as technological advancements are made ( Corley et al , 2015 ; Clark et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“… Calmet et al , 2018 ; Feng et al , 2016 ; Garcia et al , 2009 ; Keeler et al , 2015 ; Martonen and Wilson, 1983 ; Schroeter et al , 2016 ; Se et al , 2010 ). Fortunately, the time and effort to develop multiple models and perform the computational chemistry and physics processes associated with aerosols in even these complex, transient simulations continue to be reduced as technological advancements are made ( Corley et al , 2015 ; Clark et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lung mechanical modeling Lung modeling, and especially pulmonary mechanical modeling, is a great challenge given the high level of complexity of the organ and its environment [Clark et al, 2017]. A major difficulty lies in the many scales involved in pulmonary physiology and pathology, from the organ to the alveoli, through the lobe, segment, lobule and acinus scales [Burrowes et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of disease as an emergent phenomenon has gained increasing acceptance with the recognition that physiological disorders result from a convergence of abnormalities at the molecular level. 1,2 With regard to the lung, computer simulations of pulmonary emphysema have shown that disturbances at the local tissue level can lead to global structural and mechanical alterations, represented by widespread distention and rupture of alveolar walls. 3,4 In one study, a network of springs (representing elastic fibers and collagen) was modified by either increasing their stiffness or removing them entirely, resulting in architectural changes similar to those seen in pulmonary fibrosis and emphysema, respectively.…”
mentioning
confidence: 99%